RESPONSABILIDAD SOCIAL EMPRESARIAL ENFOCADA AL DESARROLLO DE UNA CULTURA INTEGRADORA DE RECICLAJE DE PAPEL DE LOS ALUMNOS DEL SEXTO Y SÉPTIMO AÑO DE EDUCACIÓN GENERAL BÁSICA DE LA UNIDAD EDUCATIVA FISCOMISIONAL “SAN FRANCISCO DE ASÍS” DE LA CIUDAD DE LOJA - Cabanilla Castro, Alex Raúl (2019)
The investigation, “SOCIAL BUSINESS RESPONSIBILITY FOCUSED ON THE DEVELOPMENT OF AN INTEGRATING CULTURE FOR THE RECYCLING OF PAPER OF THE STUDENTS OF BASIC GENERAL EDUCATION OF THE SAN FRANCISCO DE ASÍS PHYSCOMISIONAL EDUCATIONAL UNIT OF THE CITY OF LOJA”. Its objective is to carry out a culture awareness program where the values, rules, behavior, benefits of recycling, its Social Responsibility in the good use of paper and the care of the environment in the educational institution are focused. The methodology used in the development of the research work, focused on a descriptive investigation, applying observation techniques where the behavior of the students inside and outside the classrooms, the surveys of the 8 parallels of the sixth and seventh grades of education are evidenced basic general in order to obtain information from students, regarding dimensions: social, environmental and behavioral in the face of this problem that are like values, rules among others. The results obtained refer to the fact that in the 8 parallels under study it was determined that approximately 1600 pounds of paper are used in the school year; It was also determined that there is an indiscriminate use of paper by students, it was also established that there is no recycling culture on the part of those involved because they do not have an organizational culture where values, work ethics are evidenced in team to reach a level of awareness within the culture of the institution. This work is based on a theoretical framework where the concepts of several authors about social responsibility, organizational culture of values, rules, quality standards, environmental care and paper recycling are analyzed. 5 In conclusion, it is determined that the sixth and seventh year students of the San Francisco de Asís Educational Unit do not encounter a culture full of values of good behavior and rules that allow an awareness about recycling, that is, they lack knowledge and information to develop a contribution to society and the environment. It is recommended to the authorities and teachers of the institution. Execute the proposal made in this investigation. That is related to conferences, workshops, campaigns about organizational culture, recycling and environmental care, in this way we will help to better develop a culture full of values, ethical rules, equality, good use of paper and its recycling. In this way students will be contributed to be prepared in a more just and responsible way before society and our planet.